Staingan: Stain style transfer for digital histological images - Shaban, M. Tarek; Baur, Christoph; Navab, Nassir; Albarqouni, Shadi (Proceedings - International Symposium on Biomedical Imaging, 2019)
Digitized Histological diagnosis is in increasing demand. However, color variations due to various factors are imposing obstacles to the diagnosis process. The problem of stain color variations is a well-defined problem with many proposed solutions. Most of these solutions are highly dependent on a reference template slide. We propose a deep-learning solution inspired by CycleGANs that is trained end-to-end, eliminating the need for an expert to pick a representative reference slide. Our approach showed superior results quantitatively and qualitatively against the state of the art methods (10% improvement visually using SSIM). We further validated our method on a clinical use-case, namely Breast Cancer tumor classification, showing a 12% increase in AUC. The code is made publicly available 1.1https://github.com/xtarx/StainGAN.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Deep learning; Generative adversarial networks; Histology images; Stain normalization